PEDAGOGICAL CONFLICTS, WAYS TO RESOLVE THEM AND POSITIVE ASPECTS OF CONFLICTS (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes the adaptation of young teachers to teaching and conflict situations that arise in this process, and ways to eliminate them. Also, using examples from real life, ways to resolve conflicts and their positive aspects are revealed.